THE RELATIONSHIP BETWEEN ENGLISH ACHIEVEMENT OF HIGH SCHOOL STUDENTS AND THEIR PERCEPTION TOWARD ENGLISH TEACHER LEADERSHIP STYLE - Rahmat Hidayat (Universitas Jambi, 2021)
The problem of this research was how is the students' perception and is there any relationship between English achievement of high school students and their perception toward English teacher leadership style, the aims of this research were to identify students’ perception toward the teacher's leadership styles at Senior high school 1 of Talang Kelapa and to identify the relationship between English achievement and their perception toward English teacher leadership style at Senior high school 1 of Talang Kelapa. This research was conducted at Senior high school 1 of Talang Kelapa. The sample became taken through the use of stratified cluster random sampling. This research method is descriptive quantitative. For accumulating the information, this research through the use of questionnaire and documentation, all sample was given the questionnaires.